Demystifying the Female Chronic Pelvic Pain - Bhavsar, Rutuben; Malik, Kritagya (Disease and Health: Research Developments Vol. 10, 2025)
Chronic pelvic pain is one of the debilitating conditions in women that causes pain in the abdominopelvic region and affects their reproductive years of life till the postmenopausal period. It causes many difficulties in women’s lives, from work life to their personal lives, affecting them negatively. The causes of CPP can be any pathological changes in the body, such as changes in reproductive organs, musculoskeletal changes, neurological changes, or changes in genitourinary organs. Treating the underlying condition resolves the CPP; however, sometimes it takes a long time to get resolved when the neuro-musculoskeletal system is involved. There are various diagnostic evaluation methods available that help in finding out the cause of CPP and managing it. For the management of CPP, several treatment options are available, such as physical therapy, medication, and surgical procedures. However, it has been discovered that physiotherapy plays a significant role in managing CPP and preventing its recurrence.